Water Resources Development Strategy Based On Organizational Change Development - Abdul Fatah Bauw; Angky Soedrijanto; Sri Rahayu; Suprijono Wihel (RTTM, 2024)
The small population of Fakfak Regency is not an obstacle to developing businesses to manage water resources into bottled drinking water. This is based on the fact that the need for healthy drinking water is a basic need in human life. The research aims to prepare an assessment of the readiness of micro and small businesses to manage water resources into bottled drinking water in Fakfak district. Descriptive research uses a qualitative analysis approach to test the feasibility of a bottled drinking water business. Data was obtained through a simple assessment technique of respondents' opinions using the Balanced Score Card matrix as a reference. Respondents were determined deliberately, and were well known by researchers as parties who were related to water resources. Data is processed in stages using conversion techniques, weighting techniques and gap analysis. The research results show that managing water resources into bottled drinking water is not only very profitable economically, but also helps accelerate economic development for Fakfak district.